If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -3y = -12 Solving 15x + -3y = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 15x + -3y + 3y = -12 + 3y Combine like terms: -3y + 3y = 0 15x + 0 = -12 + 3y 15x = -12 + 3y Divide each side by '15'. x = -0.8 + 0.2y Simplifying x = -0.8 + 0.2y
| (7s^3-3s+3)+(s^3-6s+2)= | | y^2-625=0 | | 2x^2+2x+4=4x+4 | | -3.33+1.25= | | -13/-8= | | 6-2y+y=12 | | 4x^2-3=13 | | 1.5x+4.6=3.4x-3 | | 23w-78=76 | | -7/1.8=c | | 2-9b+3= | | 5r-(2r+8)=18 | | 2s-9s+7= | | -12/1.8=c | | 15x-21=219 | | -121+64=0 | | 7-8g-6= | | 6x+4=4(x+8) | | 7-6c+9c= | | 8m+19=9m+11 | | (x+1)/3+4=(x+7)/9 | | -3x+5x+5=11 | | 38-8x+x^2=0 | | 8+3g-2= | | 9(t+2)=2(t-2) | | -2x-4y=0 | | 10-y=2x+3 | | 3+x-14=20 | | 69-45= | | -5x-20y=-15 | | -4(w-5)=3w+6 | | 24-6n=8(7n+3) |